2018
DOI: 10.1111/mec.14518
|View full text |Cite
|
Sign up to set email alerts
|

Detecting host–parasitoid interactions in an invasive Lepidopteran using nested tagging DNA metabarcoding

Abstract: Determining the host-parasitoid interactions and parasitism rates for invasive species entering novel environments is an important first step in assessing potential routes for biocontrol and integrated pest management. Conventional insect rearing techniques followed by taxonomic identification are widely used to obtain such data, but this can be time-consuming and prone to biases. Here, we present a next-generation sequencing approach for use in ecological studies which allows for individual-level metadata tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 61 publications
0
64
1
Order By: Relevance
“…Extracted DNA samples were amplified with a vertebrate-specific primer pair (Riaz et al, 2011) that targets a 106-bp fragment of the mitochondrial 12S rRNA region in fish, using a two-step PCR protocol for library preparation that implements a nested tagging approach (Kitson et al, 2019). Previous eDNA metabarcoding studies of marine mesocosms and coastal ecosystems showed that this fragment has a low false-negative rate for bony fishes (Kelly, Port, Yamahara, & Crowder, 2014;Port et al, 2016).…”
Section: Library Preparation and Sequencingmentioning
confidence: 99%
“…Extracted DNA samples were amplified with a vertebrate-specific primer pair (Riaz et al, 2011) that targets a 106-bp fragment of the mitochondrial 12S rRNA region in fish, using a two-step PCR protocol for library preparation that implements a nested tagging approach (Kitson et al, 2019). Previous eDNA metabarcoding studies of marine mesocosms and coastal ecosystems showed that this fragment has a low false-negative rate for bony fishes (Kelly, Port, Yamahara, & Crowder, 2014;Port et al, 2016).…”
Section: Library Preparation and Sequencingmentioning
confidence: 99%
“…A double-indexed library was prepared following a 2-step PCR based protocol (Kitson et al 2018) using primers for the vertebrate 12S mitochondrial gene region (Riaz et al 2011, Kelly et al 2014. In short, an initial PCR reaction amplified the target region using individually indexed 12S primers for each sample.…”
Section: Library Preparationmentioning
confidence: 99%
“…Yet, equally importantly, we refer to the potential for handling and individual tagging (Kitson et al, 2019) of large numbers of samples, allowing the simultaneous characterization of massive numbers of ecological samples and taxa.…”
Section: Vis Ta Smentioning
confidence: 99%
“…In particular, DNA metabarcoding based on nested tagging offers unique opportunities for constructing large, highly resolved species interaction networks (Kitson et al, 2019). Generation of data on species associations without rearing the organisms involved to morphologically identifiable stages bypasses both important biases and highly laborious stages of work (Kitson et al, 2019;Koskinen et al, 2019 lives. It is also the basis for grouping nodes into more and less similar blocks within webs, and for comparing the roles of such similar blocks among regions (e.g., "the role of blowflies in different ecosystems").…”
Section: Vis Ta Smentioning
confidence: 99%